Analysis of Compliance with PPh 21 of Individual Taxpayers Case Study at PT XYZ - Hera Khairunnisa; Cindy Agustina; Ayatulloh Michael Musyaffi (Research Trend in Technology and Management, 2024)
The purpose of this study is to analyze compliance with Income Tax Article 21 (PPh 21) for individual taxpayers at PT XYZ, focusing on the calculation of Non-Taxable Income (PTKP), tax payments, and reporting. A qualitative approach was employed using a case study method, in-depth interviews, observations, and document analysis. The results indicate an error in the PTKP calculation in 2023, resulting in an overpayment of Rp 675,000. Furthermore, although tax reporting was conducted on time through the e-Filing system, the company experienced delays in tax payments, leading to administrative penalties.